Dietary Interventions Reduce Traditional and Novel Cardiovascular Risk Markers by Altering the Gut Microbiome and Their Metabolites - Vijay, Amrita; Astbury, Stuart; Panayiotis, Louca; Marques, Francine Z.; Spector, Tim D.; Menni, Cristina; Valdes, Ana M. (Frontiers in Cardiovascular Medicine, 2021)
Aims: The current study investigates the role of diet in mediating the gut microbiome-cardiovascular association which has not yet been explored in humans. Methods and Results: Using a two-arm dietary intervention study in healthy participants (N = 70), we assessed the effects of omega-3 and fibre supplementation on gut microbiome composition and short-chain fatty acid (SCFA) production. We then investigated how changes in gut microbiome composition correlated with changes in traditional cardiovascular risk factors (cholesterol, triglycerides, blood pressure), cytokines, and novel validated markers such as GlycA and ceramides, previously linked to CVD incidence and mortality. Both interventions resulted in significant drops in blood pressure, cholesterol, proinflammatory cytokines, GlycA and ceramides (all P < 0.05). Decreases in the atherogenic low-density lipoprotein triglyceride fraction, in total serum cholesterol were correlated with increases in butyric acid-production [β(SE) = −0.58 (0.06), P < 0.001; −0.53 (0.04), P < 0.001] and nominally associated with increases in some butyrogenic bacteria. Drops in GlycA were linked to increases in Bifidobacterium [β(SE) = −0.32 (0.04), P = 0.02] and other SCFAs including acetic acid [β(SE) = −0.28 (0.04), P = 0.02] and propionic acid [β(SE) = −0.3 (0.04), P = 0.02]. Additionally, we report for the first-time reductions in specific ceramide ratios that have been shown to predict CVD mortality and major adverse cardiovascular events such as d18:1/16:0, d18:0/24:0, and d18:1/24:1 which were associated with the reduction in the abundance in Colinsella and increases in Bifidobacteriuim and Coprococcus 3 and SCFAs (all P < 0.05). Conclusion: Overall, these findings support the potential of using simple dietary interventions to alter validated biomarkers linked to cardiovascular risk via the gut microbiome composition and its metabolic functions.